Wastewater treatment to enhance the economic viability of microalgae culture - J. C. M. Pires (2013)
Microalgae culture is still not economically viable and it presents some negative environmental impacts, concerning water, nutrient and energy requirements. In this context, this study aims to review the recent advances on microalgal cultures in wastewaters to enhance their economic viability. We focused on three different culture concepts: (1) suspended cell systems, (2) cell immobilization, and (3) microalgae consortia. Cultures with suspended cells are the most studied. The nutrient removal efficiencies are usually high for wastewaters of different sources. However, biomass harvesting is difficult and a costly process due to the small cell size and lower culture density. On the other hand, the cell immobilization systems showed to be the solution for this problem, having as main limitation the nutrient diffusion from bulk to cells, which results in a reduced nutrient removal efficiency. The consortium between microalgae and bacteria enhances the growth of both microorganisms. This culture concept showed to be a promising technology to improve wastewater treatment, regarding not only nutrient removal but also biomass harvesting by bioflocculation. The aggregation mechanism must be studied in depth to find the process parameters that would lead to an effective and cheap harvesting process.